PENGARUH IMPLEMENTASI PRINSIP-PRINSIP GOOD GOVERNANCE TERHADAP KINERJA ORGANISASI (Suatu Studi Di Dinas Perindustrian Dan Perdagangan Kota Manado) - Setiadi, Adi; KIYAI, Burhanuddin; RURU, JOORIE MARHAEN (Sam Ratulangi University, 2015)
Abstract : This research moved from the problem that the performance of the Department ofIndustry and Trade organization Manado indicated relatively low. This is presumably related to theapplication of the principles of good governance do not optimal. Thus, this study aims to: (1). Todescribe the application / implementation of the principles of good governance. (2). To describealso the achievement of the organization's performance; and (3). To analyze the effect of theapplication / implementation of the principles of good governance to organizational performanceDepartment of Industry and Trade of Manado.By using a quantitative approach and descriptive method, data were collected throughquestionnaires distributed technique to 30 employees and 30 respondents respondents were fromindustry and commerce businesses. Once the data is collected, then processed and analyzed usingdescriptive analysis techniques stratisk (Table freuensi) to describe the variable-varabel research isconducted and to test the hypothesis applied inferential statistical analysis techniques (correlationand regression analysis).The results showed that (1) the application of the principles of participation, according to therespondents' assessment of employees are in the category of